PROSPEK PENGEMBANGAN AGROWISATA SEBAGAI WISATA ALTERNATIF DI DESA PELAGA - Ni Wayan Wahyu Astuti (Politeknik Negeri Bali, 2013)
Development of the tourism sector in the province of Bali need to be developed in accordance with the conditions, potential and resources owned by each district in Bali. Tourism in fairly rapid growth requires new breakthroughs in anticipation of the saturation that may occur on tourists. Then came the development of tourism opportunities that promote the preservation of the natural environment in order to prevent destruction and/or environmental pollution caused by tourism activities, better known as the